2024
DOI: 10.3389/fphys.2023.1344885
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell therapy for heart failure in the clinics: new perspectives in the era of precision medicine and artificial intelligence

Mohammed A. Chowdhury,
Jing J. Zhang,
Rodrigue Rizk
et al.

Abstract: Stem/progenitor cells have been widely evaluated as a promising therapeutic option for heart failure (HF). Numerous clinical trials with stem/progenitor cell-based therapy (SCT) for HF have demonstrated encouraging results, but not without limitations or discrepancies. Recent technological advancements in multiomics, bioinformatics, precision medicine, artificial intelligence (AI), and machine learning (ML) provide new approaches and insights for stem cell research and therapeutic development. Integration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 146 publications
0
2
0
Order By: Relevance
“…Gene enrichment analysis indicated that MAP7D3 is not only linked to angiogenesis but also to stem cell pathways. Stem cells are precursor cells that have the ability to self-renew and differentiate into functionally mature, specialized cells in various human tissues Stem cells are precursor cells that have the ability to self-renew and differentiate into functionally mature special cells in various tissues of the human body ( 45 ). Importantly, evidence suggests that the interplay between tumor angiogenesis and cancer stem cells promotes tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Gene enrichment analysis indicated that MAP7D3 is not only linked to angiogenesis but also to stem cell pathways. Stem cells are precursor cells that have the ability to self-renew and differentiate into functionally mature, specialized cells in various human tissues Stem cells are precursor cells that have the ability to self-renew and differentiate into functionally mature special cells in various tissues of the human body ( 45 ). Importantly, evidence suggests that the interplay between tumor angiogenesis and cancer stem cells promotes tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is evidence to suggest that circulating monocyte levels could serve as a biomarker for metastatic PRAD, indicating a notably unfavorable prognosis (12). Integrated multi-omics, machine learning, and artificial intelligence are being more frequently utilized in the field of medicine (13)(14)(15)(16)(17). It is essential to conduct further analysis on levels of tumorinfiltrating immune cells and identify genes related to immune cell infiltration using multi-omics and machine learning techniques to enhance the accuracy of diagnosis and treatment for PRAD.…”
Section: Introductionmentioning
confidence: 99%